2014
DOI: 10.1177/1074248414532013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cannabidiol on Ischemia/Reperfusion-Induced Ventricular Arrhythmias

Abstract: Cannabidiol (CBD) is a nonpsychoactive phytocannabinoid with anti-inflammatory activity mediated by enhancing adenosine signaling. As the adenosine A1 receptor activation confers protection against ischemia/reperfusion (I/R)-induced ventricular arrhythmias, we hypothesized that CBD may have antiarrhythmic effect through the activation of adenosine A1 receptor. Cannabidiol has recently been shown to suppress ischemia-induced ventricular arrhythmias. We aimed to research the effect of CBD on the incidence and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 40 publications
0
67
0
7
Order By: Relevance
“…CBD (50 μg/kg) inhibits the subsequent ventricular tachycardia following coronary artery occlusion in rats-an effect abolished by 8-cyclopentyl-1,3-dipropylxanthine, an adenosine A 1 receptor antagonist (Table 1). These results demonstrate that CBD can exert an antiarrhythmic effect, possibly mediated by the adenosine A 1 receptor [36]. In addition to effects on the A 1 receptor, A 2 receptor-mediated effects of CBD have also been reported and claimed to mediate antiinflammatory effects of CBD [10,31,37,38].…”
Section: Adenosinementioning
confidence: 64%
“…CBD (50 μg/kg) inhibits the subsequent ventricular tachycardia following coronary artery occlusion in rats-an effect abolished by 8-cyclopentyl-1,3-dipropylxanthine, an adenosine A 1 receptor antagonist (Table 1). These results demonstrate that CBD can exert an antiarrhythmic effect, possibly mediated by the adenosine A 1 receptor [36]. In addition to effects on the A 1 receptor, A 2 receptor-mediated effects of CBD have also been reported and claimed to mediate antiinflammatory effects of CBD [10,31,37,38].…”
Section: Adenosinementioning
confidence: 64%
“…Different studies revealed that this phytocannabinoid acts as a full 5HT 1A agonist, a 5HT 2A weak partial agonist and a non-competitive antagonist of 5HT 3A [4850]. The ability of CBD to activate the A 1A adenosine receptors has also been proposed [51]. Its activity at these receptors could mediate the anti-inflammatory and immunosuppressive effects of CBD.…”
Section: Pharmacology Of Selected Phytocannabinoidsmentioning
confidence: 99%
“…Previous research has reported that miRNAs and Cx43 take part in the formation of RA [20], while the correlation mechanism between the two is rarely investigated in detail. Apart from ventricular arrhythmia, upward shift of the S-T segment, and QT prolongation, the ECG also exhibited prolonged QRS interval after ischemia reperfusion, all of which are associated with a slower intermyocardial conduction velocity after ischemia reperfusion [21]. GJ, as the basic structure of cardiac electrophysiology, maintains the normal coupling in EGC signals and mechanical coupling by mediating intercellular electrochemical 10 communications.…”
Section: Discussionmentioning
confidence: 98%